Paratext and Megatext as Channels of Jewish and Christian Traditions : The Textual Markers of Contextualization - Hollander, August den; Schmid, Ulrich; Smelik, Willem (Jewish and Christian Perspectives Series, 2003)
Religious traditions are channeled to new audiences by textual markers, which inform their understanding and influence. Such markers are signs of contextualisation which belong to the paratext of a tradition: textual elements that do not belong to the core text itself but belong to their embedding and as such affect their reception. Alternatively, some texts function purposely in tandem with another text, and cannot be understood without that text. While the second text informs the way the first one is being understood, it can hardly function independently. The discussions include the arrangement of textual blocks in the Hebrew Bible; how the oral transmission of Jewish Aramaic Bible translations had to be recited as a counterpoint to the Hebrew chant; how synagogue poetry presupposes the channels of liturgical instruction; how the Talmud can be perceived as a translation of Mishnah; how the presence of paratextual elements such as annotations and prefaces influenced the Index Librorum Prohibitorum concerning 16th century Bibles; the function of paratext and scope for modern Bible translations. This volume will tentatively explore the wide range of paratext and megatext as devices of channeling religious traditions.